Effects of skeletal unloading on the bone marrow antibody repertoire of tetanus toxoid and/or CpG treated C57BL/6J mice. (August 2019) - Rettig, Trisha A.; Nishiyama, Nina C.; Pecaut, Michael J.; Chapes, Stephen K.
Highlights: Use of a physiological model (AOS) of spaceflight alters the bone marrow antibody repertoire. Tetanus toxoid ± CpG with or without AOS alters the bone marrow antibody repertoire. Class switched V-gene segment usage differs from whole repertoire VH-gene segment usage. Abstract: Spaceflight is known to impact the immune system in multiple ways. However, its effect on the antibody repertoire, especially in response to challenge, has not been well characterized. The development of the repertoire has multiple steps that could be affected by spaceflight, including V-(D-)J-gene segment rearrangement and the selection of complementarity determining regions (CDRs); specifically, CDR3, responsible for much of the diversity in the repertoire. We used skeletal unloading with the antiorthostatic suspension (AOS) model to simulate some of the physiological effects associated with spaceflight. Animals ± AOS were challenged with tetanus toxoid (TT) and/or CpG, an adjuvant. Two weeks after challenge, bone marrow was collected and sequenced using the Illumina MiSeq 2 × 300 platform. The resulting antibody repertoire was characterized, including V-, D- (heavy only), and J-gene segment usage, constant region usage, CDR3 length, and V(D)J combinations. We detected changes in gene-segment usage in response to AOS, TT, and CpG treatment in both the heavy and light chains. Additionally, changes were seen in the class-switched VH-gene repertoire. Alterations were also detected in V/J pairing for both the heavy and light chains, and changes in CDR3 length. We also detected lower levels of CDR3 AA overlap than detected in the splenic repertoire. These results demonstrate that AOS, TT, and CpG alter the bone marrow antibody repertoire however, it is still unclear from the data whether there is a loss of host antigen-specific responsiveness because of the change in gene use.